Using Brochures in Teaching Vocabulary to Improve Students’ Vocabulary Mastery in English for Hotel - .,, Melvina (TELL - US JOURNAL, 2015)
This paper discussed about using brochures in teaching vocabulary to improve students’ vocabulary mastery in English for Hotel. Many problem faced by students in teaching and learning process, especially in mastering vocabulary about hotel. For instance, they still did mistakes not only in identifying the vocabulary about hotel in performing but also in written test. While, in outside when they did casual job in hotel they also faced crucial problems about their performance. They got difficult in label stuff of hotel and sometimes they do mistakes in doing work because they did not know the meaning of vocabularies of hotel. There are two potential causes of the condition; they are students and the lesson material. First from the student’s side, it can be caused of lack of motivation in learning English. They are still not realized that EFH is very important for their major. They will engage with English in their work situation.  The second problem is about material. We still find a number of teachers used General English book in teaching EFH.  Using authentic material in teaching and learning can be used to improve student’s vocabulary mastery in EFH. Brochure is one of authentic material and it also a kind of visual media aids that can help teacher and students in improving students’ vocabulary mastery in English for Hotel.